Long-term disability in neuromyelitis optica spectrum disorder with a history of myelitis is associated with age at onset, delay in diagnosis/preventive treatment, MRI lesion length and presence of symptomatic brain lesions - Mealy, MA; Mossburg, SE; Kim, S-H; Messina, S; Borisow, N; Lopez-Gonzalez, R; Ospina, JP; Scheel, M; Yeshokumar, AK; Awad, A; Leite, MI; Arango, JJ; et al. (Elsevier, 2018)
BACKGROUND:Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune disease of the central nervous system (CNS) that preferentially targets the spinal cord and optic nerves. Increasing disability is accrued with each inflammatory attack. Disability has been shown to be an independent predictor of poor quality of life in those with NMOSD. Factors associated with increasing disability need further systematic investigation. METHODS:We performed a multi-center retrospective chart analysis of aquaporin-4 (AQP4) seropositive NMOSD patients with a history of myelitis seen at five large referral centers for patients with NMOSD worldwide for whom thorough records including relapse history and corresponding imaging were available. Potential contributors to long-term disability were extracted including demographics, radiographic findings, and clinical characteristics. Multivariable regression modeling was conducted to determine correlates of disability in patients with NMOSD, as measured by the Expanded Disability Status Scale (EDSS). RESULTS:One hundred eighty-two AQP4 seropositive patients (88% female) were included in this analysis. Multiple regression modeling revealed that older age at disease onset, delay in diagnosis/preventive treatment, length of longest acute myelitis lesion and presence of symptomatic brain/brainstem lesions were associated with increased disability when holding other variables constant. CONCLUSION:While age at onset is a factor that cannot be controlled in NMOSD, we can reduce the delay in diagnosis/preventive treatment and reduce future relapses in the brain/brainstem and spinal cord. Delay in diagnosis/preventive treatment and imaging variables that contributed to increased disability support the need for improved measures for early, accurate diagnosis and management of NMOSD, and aggressive treatment of acute relapses.